PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PT. PLN (Persero) AREA DUMAI RAYON DURI KABUPATEN BENGKALIS - Rustami, Rustami; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to determine the effect of leadership, organizationalcommitment on job satisfaction and performance of employees of PT. PLN (Persero)Rayon Area Dumai Rayon Duri Bengkalis Regency. Responden are employees of PT.PLN (Persero) Area Dumai Rayon Duri Bengkalis Regency is 104 people.Theindependent variables consist of leadership, organizational commitment, and jobsatisfaction as an intervening variable. While the dependent variable is the performanceof employees, hypothesis testing was done using a model path anlysis.The results showthat there is a positive and significant influence directly the leadership andorganizational commitment to job satisfaction. Furthermore, there are also positive andsignificant influence directly the leadership and organizational commitment to employeeperformance, whereas no significant effect on job satisfaction. Then the influence ofleadership and organizational commitment indirectly to employee performance throughjob satisfaction has positive influence that job satisfaction as an intervening variable canimprove employee performance.